Accessory Pathway Ablation Located Just Below The Bundle of His: A Challenging Case - Puspa Lestari; Ardian Rizal; Yoga Waranugraha (Heart Science Journal, 2020)
We presented a case of Wolff-Parkinson-White (WPW) Syndrome. A 69-year-old man was admitted for evaluation of frequent episodes of palpitation. The diagnosis of WPW syndrome was established based on the 12-lead surface electrocardiogram (ECG) and electrophysiology (EP) study. We conducted the radiofrequency ablation (RFA) to the accessory pathway (AP). The challenging point of this case was the accessory pathway located just below to the bundle of His, which is related to the risk of complete atrioventricular (AV) block. In summary, we conclude that anatomical consideration, EP study, and the ablation strategy were important to improve the safety and success rate of RFA procedure.